Human pharmacokinetics of xanthohumol, an antihyperglycemic flavonoid from hops. Issue 2 (27th August 2013) - Legette, LeeCole; Karnpracha, Chanida; Reed, Ralph L.; Choi, Jaewoo; Bobe, Gerd; Christensen, J. Mark; Rodriguez‐Proteau, Rosita; Purnell, Jonathan Q.; Stevens, Jan F.
<x xml:space="preserve">Abstract</x> Scope Xanthohumol (XN) is a bioactive prenylflavonoid from hops. A single‐dose pharmacokinetic (PK) study was conducted in men (n = 24) and women (n = 24) to determine dose–concentration relationships. Methods and results Subjects received a single oral dose of 20, 60, or 180 mg XN. Blood was collected at 0, 0.25, 0.5, 1, 2, 4, 8, 12, 24, 48, 72, 96, and 120 h. Plasma levels of XN and its metabolites, isoxanthohumol (IX), 8‐prenylnaringenin (8PN), and 6‐prenylnaringenin (6PN) were measured by LC‐MS/MS. Xanthohumol (XN) and IX conjugates were dominant circulating flavonoids among all subjects. Levels of 8PN and 6PN were undetectable in most subjects. The XN PK profile showed peak concentrations around 1 h and between 4–5 h after ingestion. The maximum XN concentrations (Cmax) were 33 ± 7 mg/L, 48 ± 11 mg/L, and 120 ± 24 mg/L for the 20, 60, and 180 mg dose, respectively. Using noncompartmental modeling, the area under the curves (AUC0→∞) for XN were 92 ± 68 h × μg/L, 323 ± 160 h × μg/L, and 863 ± 388 h × μg/L for the 20, 60, and 180 mg dose, respectively. The mean half‐life of XN was 20 h for the 60 and 18 h for the 180 mg dose. Conclusion XN has a distinct biphasic absorption pattern with XN and IX conjugates being the major circulating metabolites.